Intrathecal hydromorphone as an analgesia option for gynecology patients. Issue 8 (August 2020) - Gajarawala, Shilpa; Wells, Ali; Watkins, Elyse; Rust, Bartley; Archambault, Mark
Abstract : ABSTRACT: Enhanced recovery after surgery (ERAS) is a multimodal perioperative strategy originally developed to attenuate the postsurgical stress response in patients after colorectal surgery. Patients undergoing gynecologic surgery who had ERAS had significantly shorter hospital length of stay, reduced hospital-related costs, and acceptable pain management with reduced opioid use, without compromising patient satisfaction. Intrathecal hydromorphone is an effective alternative ERAS protocol analgesia for these patients and will not compromise patient outcomes or healthcare costs.